Water, Sustainability and Poetics in the Works of the cAt Group - Sogabe, Milton Terumitsu; Fogliano, Fernando; Hildebrand, Hermes Renato; Nunes, Fabio Oliveira [UNESP]; Rubini, Tiago [UNESP]; Braz, Soraya [UNESP]; Marques, Rodrigo Dorta [UNESP]; Steinberg, Mirian [UNESP]; Carvalho, Roberta [UNESP]; Crispim, Danilo [UNESP]; Malva, Daniel [UNESP]; dos Santos, Caio Netto [UNESP]; et al. (Association for Computing Machinery (ACM), 2021)
The article discusses art-technology productions related to concepts such as the Anthropocene, Chthulecene and Plantationocene. More specifically, it regards artworks related to sustainability, the use of water and alternative energy. In this sense some artworks from a number of artists are analyzed in the text, discussing the presence of water as a poetic element in the History of Art, to then think about water in the context of sustainability. More importantly, the paper talks about the cAt (science, Art, technology) group working with water in its solid, liquid and gaseous states as poetic forms, respectively, in each of the group’s artworks presented below. The pieces “Sopro”, “Toque” and “Gesto” were idealized as minimalist ways with which the public can interact using common abilities of the human body to generate electric energy. These artworks’ systems are simple, displayed inside transparent structures and do not require computers or electric energy delivered from regular and commercial sources.
Keywords: Art-Technology; CAt group; Sustainability; Water